(untitled) (Journal of Environmental Science and Natural Resources, 2017)
The study was conducted to asses the aquatic faunal diversity in the Ratargul Swamp Forest during the period from November 2014 to October 2015. For the systematic study of aquatic fauna, the quadrate method along with transect was used where 4 transects were selected in the swamp forest each with 5 stations based on topography and vegetation. A total of 24 species of aquatic fauna belonging to 18 families were identified during the period, which were crustaceans (7), molluscs (4), fishes (12) and annelid (1). Among them, fishes were the most dominant and abundant groups. The crustaceans, molluscs, fishes and annelid were shown different pattern of density and diversity within the Transects. The density of individuals in Ratargul Swamp Forest varied from station to station within a range of 8 to 40 Indm-². The lowest Simpsons Index of Diversity was 2.76 in T-4, which was situated in the transitional area between forested land and relatively deep lake within the forest. Leptocarpus potamiscus, Nandus nandus, and Pila globosa were the dominant shrimp, fish and mollusc species in the T-4, respectively. The highest Simpsons Index of Diversity was 3.89 in T-3, which was situated along the bank of a small channel within the forest. Nematopalaemon tenuipes, Puntius ticto, and Pila globosa were the dominant shrimp, fish and mollusc species in T-3, respectively. J. Environ. Sci. & Natural Resources, 9(2): 51-64 2016